Pharmacokinetics, metabolism, and excretion of cycloastragenol, a potent telomerase activator in rats. (3rd June 2017) - Ma, Peng-Kai; Wei, Bao-Hong; Cao, Yan-Ling; Miao, Qing; Chen, Ning; Guo, Chang-E; Chen, Hong-Ying; Zhang, Yu-Jie
Abstract: 1. The objective of this study was to investigate the pharmacokinetics, excretion, and metabolic fate of cycloastragenol (CA) in rats. 2. An LC-MS method was developed and used to quantify CA in biological samples. Rats were orally administrated with CA at 10, 20, and 40 mg/kg or intravenously administrated at 10 mg/kg to determine pharmacokinetic parameters of CA. For excretion experiment, urine, feces, and bile were collected at 24 h after oral administration (40 mg/kg), also at 12 h after intravenous administration (10 mg/kg). An LC-MS/MS method was developed to identify the metabolites of CA. 3. The results showed that the oral bioavailability of CA was about 25.70% at 10 mg/kg. CA was excreted through bile and feces and eliminated predominantly by the kidney in rats. It also might exist an enterohepatic circulation of CA in rats. CA could be metabolized widely in vivo in rat, seven, six, and one phase I metabolites were found in feces, urine, and bile samples respectively, but no phase II metabolite was found. 4. In summary, this study defined pharmacokinetics characteristics of CA, described its excretion, and established its in vivo metabolism in rats.